2021
DOI: 10.2991/assehr.k.211223.056
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Model for Health-Related Fitness Status Using Discriminant Analysis

Abstract: Physical fitness represents the well-being of an individual and figures in measuring individual daily activities. This research aims to differentiate the physiological variables in distinguishing man fitness status without physical tests. The subjects of the examination amounted to 60 men aged 17-23 years old. The physiological parameters were age, weight, height, resting heart rate, blood glucose level, blood pressure, and VO2max, a bio-motoric component, measured by cooper protocol, running for 2.4 km. Subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Heart rate is the easiest but most effective indicator to use in exercise monitoring (Djaoui et al, 2017;Foster et al, 2017). Apart from that, hearing rate is also a valid predictor of someone's fitness (Pramono et al, 2021). The heart rate mechanism is an indicator of fitness based on the performance of the sympathetic and parasympathetic nerves, which work during exercise and rest.…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate is the easiest but most effective indicator to use in exercise monitoring (Djaoui et al, 2017;Foster et al, 2017). Apart from that, hearing rate is also a valid predictor of someone's fitness (Pramono et al, 2021). The heart rate mechanism is an indicator of fitness based on the performance of the sympathetic and parasympathetic nerves, which work during exercise and rest.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that only resting heart rate and standing board jump differed from the control group. The Resting heart rate component is very important to continuously monitor its development because it is directly related to indicators of a person's fitness development (Pramono et al, 2021;Quan et al, 2014). Changes in heart rate are influenced by the type of exercise a person does (Perrone et al, 2021); included in this study were differences in changes in heart rate influenced by exercise using the Tabata method and not using the Tabata method.…”
Section: Discussionmentioning
confidence: 99%